A Social Learning Approach to Prescription Drug Misuse Among College Students. Issue 6 (2nd June 2016) - Watkins, William C.
ABSTRACT: Within the current body of literature on prescription drug misuse (PDM), there is a notable disparity between the number of descriptive and theoretically based studies looking at this phenomenon. This study seeks to add, specifically, to the latter category by examining PDM among a sample of undergraduate college students at a large, southern university using the tenets of social learning theory to identify potential risk factors for misuse. Findings indicate partial support for the ability of social learning theory to explain prescription drug misuse, particularly through the scopes of differential association and differential reinforcement. Implications and future directions are discussed.